A new catalytic material MXene / ZnMnO 3 And preparation method thereof
The ball milling method was used to embed ZnMnO3 between the layers of MXene material, which solved the problem of insufficient performance of metal-air battery catalysts and significantly improved the ORR performance of the catalyst.
Patent Information
- Application Number
- CN202210901316.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-28
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-07-28
AI Technical Summary
The prior art has not yet found an excellent catalyst in metal-air batteries, resulting in problems such as reaction overpotentials, and few research has been conducted on MXene materials as support to load perovskite metal oxides.
MXene/ZnMnO3, a catalytic material supported by MXene material, was prepared by ball milling, and aging reaction was performed using a mixed solution of Zn(NO3)2·6H2O and MnSO4·H2O and Na2CO3 solution to form precipitation after the precipitation Washing, drying, calcining and ball milling were carried out, and intercalating between the layers of ZnMnO3 to MXene.
The specific surface area, pore capacity and average pore size of ZnMnO3 are improved, the paths of ion diffusion and charge transport are widened, the electrochemical performance of MXene materials is improved, and the overall catalytic performance of the catalyst is significantly improved, and the oxygen reduction reaction (ORR) is significantly improved. )performance.
Smart Images

Figure CN115275224B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy catalysts, and in particular to a new catalytic material MXene / ZnMnO3 and a preparation method thereof. Background Art
[0002] With the development of society and the advancement of science and technology, environmental pollution has become one of the key issues of social concern, thus promoting the development of new energy technologies. The research and development of new energy materials is one of the factors that affect the speed of development of new energy technologies.
[0003] Among them, metal-air batteries have broad application prospects in the field of energy storage due to their advantages such as high specific energy, stable performance and relatively stable price. However, metal-air batteries currently still have problems such as high reaction overpotential, and finding excellent catalysts is an effective way to solve these problems.
[0004] At present, most studies focus on materials prepared by different preparation methods of perovskite compounds and M materials, and study their properties and related applications; for example, Chinese patent (CN105152220A) discloses a method for preparing spinel lithium manganese oxide by ball milling, which includes preparing MnCO3 with MnSO4 as the base liquid, then roasting MnCO3 into manganese oxide, and then adding hydrogen peroxide to obtain a precursor, and then obtaining spinel lithium manganese oxide with good performance through ball milling and calcination. Naguib et al. used hydrofluoric acid etching to etch MAX phase Ti3AlC2 to prepare two-dimensional Ti3C2T x ; However, its ORR performance is still relatively low. At present, there are very few studies on MXene materials as carriers, loaded with perovskite-type metal oxides and used as air electrode catalysts for metal-air batteries. Most of the MXene materials are used in supercapacitors, lithium-ion batteries, lithium-sulfur batteries, solar cells, sensors, photocatalysis, electronic information, etc.
[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a new catalytic material MXene / ZnMnO3 and a preparation method thereof, aiming to solve the problem of how to use the ball milling method to prepare perovskite-type oxide ZnMnO3 loaded with MXene material as a carrier.
[0007] The technical solution of the present invention is as follows:
[0008] A method for preparing a novel catalytic material MXene / ZnMnO3 comprises the following steps:
[0009] Prepare a mixed solution of Zn(NO3)2·6H2O and MnSO4·H2O; prepare a Na2CO3 solution;
[0010] Using deionized water as the base liquid, dripping the mixed solution and the Na2CO3 solution into the base liquid and stirring, and generating a precipitate through an aging reaction;
[0011] The precipitate is washed and centrifuged, and then dried to obtain a precursor powder;
[0012] The precursor powder is ground, calcined, and then ground to obtain ZnMnO3;
[0013] Ball milling the ZnMnO3, MXene material and solvent;
[0014] The ball-milled material is collected, washed and dried to obtain the MXene / ZnMnO3.
[0015] The preparation method of the novel catalytic material MXene / ZnMnO3, wherein the mixed solution [Zn 2+ ] and [Mn 2+ ] is 1:1; the metal ions [Zn 2+ ] and [Mn 2+ ] The total concentration is 0.05~0.5mol / L.
[0016] The preparation method of the new catalytic material MXene / ZnMnO3, wherein the concentration of the Na2CO3 solution is 0.1-1 mol / L.
[0017] The preparation method of the new catalytic material MXene / ZnMnO3, wherein the concentration of the Na2CO3 solution is greater than the concentration of the mixed solution, and the concentration ratio of the mixed solution to the Na2CO3 solution is 1:(2~3).
[0018] The preparation method of the novel catalytic material MXene / ZnMnO3, wherein the speed ratio of the mixed solution and the Na2CO3 solution dripping into the base liquid is 2:(3-4).
[0019] The preparation method of the novel catalytic material MXene / ZnMnO3, wherein the mixed solution and the Na2CO3 solution are dripped into the base liquid at a rate of 2-6 mL / min and 3-9 mL / min respectively, and stirred for 2-4 hours.
[0020] The preparation method of the novel catalytic material MXene / ZnMnO3, wherein the aging reaction time is 2 to 6 hours.
[0021] The preparation method of the novel catalytic material MXene / ZnMnO3, wherein the calcination treatment comprises the steps of:
[0022] The precursor powder is ground, placed in a muffle furnace and heated to 700-900° C., and the calcination time is 2-8 hours.
[0023] The preparation method of the novel catalytic material MXene / ZnMnO3, wherein the ZnMnO3 and MXene material are ball-milled with anhydrous ethanol in a mass ratio of 1:1, the ball-milling time is 14 to 26 hours, and the ball-milling speed is 280 to 320 rpm.
[0024] A new catalytic material MXene / ZnMnO3 is prepared by using the preparation method of the new catalytic material MXene / ZnMnO3.
[0025] Beneficial effects: The present invention provides a new catalytic material MXene / ZnMnO3 and a preparation method thereof. The new catalytic material MXene / ZnMnO3 is prepared by ball milling, and the zinc manganate in MXene / ZnMnO3 has an irregular particle structure; the ball milling method is used to prepare the MXene material as a carrier, and the perovskite-type oxide ZnMnO3 is embedded in the interlayer, so that the specific surface area, pore volume and average pore size of ZnMnO3 are significantly improved, and the interlayer spacing can be increased while maintaining the layered structure of the MXene material, the path of ion diffusion and charge transfer is widened, and the electrochemical performance of the MXene material is improved, thereby improving the overall catalytic performance of the catalyst. By comparing the polarization curves, it can be seen that after adding the MXene material, its limiting current density increases significantly, and the ORR performance is greatly improved compared to pure zinc manganate. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a process flow chart of a preparation method of a novel catalytic material MXene / ZnMnO3 of the present invention;
[0027] Figure 2 The scanning electron microscope images of MXene / ZnMnO3 prepared in Example 1 of the present invention at different magnifications, including (a) 50,000 times, (b) 100,000 times, (c) 300,000 times, and (d) 400,000 times;
[0028] Figure 3 X-ray powder diffraction patterns of ZnMnO3 and MXene / ZnMnO3 prepared in Comparative Example 1 and Example 1 of the present invention, respectively;
[0029] Figure 4 (a) is the N2 adsorption-desorption curve of ZnMnO3 prepared in Comparative Example 1 of the present invention; Figure 4(b) is the N2 adsorption-desorption curve of MXene / ZnMnO3 prepared in Example 1 of the present invention;
[0030] Figure 5 The pore size distribution curves of ZnMnO3 and MXene / ZnMnO3 prepared in Comparative Example 1 and Example 1 of the present invention, respectively;
[0031] Figure 6 (a) is a CV curve diagram of ZnMnO3 and MXene / ZnMnO3 prepared in Comparative Example 1 and Example 1 of the present invention, respectively; Figure 6 (b) is the ORR polarization curve diagram of ZnMnO3 and MXene / ZnMnO3 prepared in Comparative Example 1 and Example 1 of the present invention, respectively. DETAILED DESCRIPTION
[0032] The present invention provides a novel catalytic material MXene / ZnMnO3 and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0033] In the embodiments and the scope of the patent application, unless the text specifically defines the article, "a", "an", "the" and "the" may also include plural forms. If there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features.
[0034] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.
[0035] MXene materials are a new type of two-dimensional layered transition metal carbides or nitrides, obtained by etching the A element in the ternary layered ceramic material MAX. Among the many cathode catalysts, precious metals and their oxides, and perovskite metal oxides all show very excellent performance, but the price of precious metals is relatively expensive, which is not conducive to the marketization of air batteries; therefore, perovskite metal oxides have become one of the most promising catalyst materials in the field of air batteries due to their low cost, easy access, high performance, and pollution-free advantages.
[0036] However, there is currently little research at home and abroad on using MXene materials as carriers, loading perovskite-type metal oxides and using them as air electrode catalysts for metal-air batteries. Instead, MXene materials are used in supercapacitors, solar cells, electronic information fields, etc.
[0037] Based on this, please refer to Figure 1 The present invention provides a method for preparing a novel catalytic material MXene / ZnMnO3, comprising the steps of:
[0038] Step S10: preparing a mixed solution of Zn(NO3)2·6H2O and MnSO4·H2O; preparing a Na2CO3 solution;
[0039] Step S20: using deionized water as the base liquid, dropping the mixed solution and the Na2CO3 solution into the base liquid and stirring, and generating a precipitate through an aging reaction;
[0040] Step S30: washing and centrifuging the precipitate, and then drying it to obtain a precursor powder;
[0041] Step S40: grinding the precursor powder, calcining it, and then grinding it to obtain ZnMnO3;
[0042] Step S50: ball milling the ZnMnO3, MXene material and solvent;
[0043] Step S60: collecting the ball-milled material, washing and drying it to obtain the MXene / ZnMnO3.
[0044] In this embodiment, MXene material is used as a carrier, and the perovskite catalyst material is embedded in the interlayer of MXene to prepare a nanocomposite material. This not only does not destroy the layered structure of MXene, but also increases the distance between layers and increases the specific surface area of the catalyst, thereby widening the path of ion diffusion and charge transfer, and improving the electrochemical properties of the MXene material, thereby achieving the purpose of improving the overall catalytic performance of the catalyst. Among them, the ball milling method is used to prepare the catalytic material MXene / ZnMnO3 with MXene material as the carrier and loaded with the perovskite oxide ZnMnO3. The two materials are mixed more thoroughly by ball milling. During the long-term ball milling process, the MXene changes from an accordion-like structure to fragments, and the zinc manganate changes from a spherical shape to smaller irregular particles. There will be physical adhesion or partial coating between the two materials. The ZnMnO3 can be evenly attached to the surface of the MXene and distributed between the layers, and it is not easy to fall off. It has good catalytic performance and is very beneficial to environmental protection. It has the advantages of good reproducibility, low cost, large output, simple operation, pollution-free preparation process, and easy to realize large-scale industrial production.
[0045] Specifically, deionized water is used as the base liquid, the mixed solution and the Na2CO3 solution are respectively dripped into the base liquid at different speeds and stirred, and a white precipitate is generated through an aging reaction; then, the white precipitate is washed with anhydrous ethanol and deionized water, and the white precipitate is collected after centrifugation, and the white precipitate is placed in an oven until it is completely dried to obtain a white powder precursor; the precursor powder is ground and calcined, and then ground again to obtain black powder ZnMnO3.
[0046] In some embodiments, the mixed solution [Zn 2+ ] and [Mn 2+ ] is 1:1; the metal ions [Zn 2+ ] and [Mn 2+ ] is 0.05~0.5mol / L. In order to ensure that the raw materials are not wasted and the required products can be prepared, Zn is selected 2+ With Mn 2+ The molar ratio is 1:1. Too high a ratio will easily waste raw materials, and the concentration range can be enlarged according to the ratio.
[0047] In a preferred embodiment, the metal ions [Zn 2+ ] and [Mn 2+ The total concentration of ] is 0.1-0.3 mol / L. The concentration range can be further enlarged according to the actual production situation, and this concentration range can make the reaction more complete.
[0048] In some embodiments, the concentration of the Na2CO3 solution is 0.1 to 1 mol / L.
[0049] In a preferred embodiment, the concentration of the Na2CO3 solution is 0.2-0.6 mol / L. Selecting this concentration range can allow for a more complete reaction, so that Zn in the solution 2+ and Mn 2+ Precipitate as much ZnMnO3 as possible.
[0050] In some embodiments, the concentration of the Na2CO3 solution is greater than that of the mixed solution, and the concentration ratio of the mixed solution to the Na2CO3 solution is 1:(2-3). As a preferred embodiment, the concentration ratio of the mixed solution to the Na2CO3 solution is 1:2.
[0051] In some embodiments, to ensure that the reaction environment is alkaline, the speed at which the Na2CO3 solution is dripped into the base liquid is greater than the speed at which the mixed solution is dripped into the base liquid. Specifically, the ratio of the speed at which the mixed solution and the Na2CO3 solution are dripped into the base liquid is 2:(3-4).
[0052] In some embodiments, the mixed solution and the Na2CO3 solution are dripped into the base liquid at a rate of 2-6 mL / min and 3-9 mL / min, respectively, and stirred for 2-4 h; wherein the speed ratio of the mixed solution and the Na2CO3 solution dripped into the base liquid satisfies 2:(3-4).
[0053] In a preferred embodiment, the drop speed of the mixed solution is 3-4 mL / min, the drop speed of the Na2CO3 solution is 4-6 mL / min, and the drop speed ratio of the mixed solution to the Na2CO3 solution is 2:3. The preferred drop speed can make the reaction fully proceed. Too fast drop speed will make the mixed solution insufficient and uneven. Too slow drop speed will increase the preparation cycle and reduce the preparation efficiency. It has been determined by experiments that a drop ratio of 2:3 can make the reaction more uniform and thorough in an alkaline environment.
[0054] In some embodiments, the aging reaction time is 2 to 6 hours. As a preferred embodiment, the aging reaction time is 3 to 5 hours.
[0055] In some embodiments, the calcination treatment comprises the steps of grinding the precursor powder, placing it in a muffle furnace and heating it to 700-900° C., and calcining it for 2-8 hours.
[0056] As a preferred embodiment, the calcination treatment comprises the steps of: grinding the precursor powder, placing it in a muffle furnace and heating it to 750-850° C., and calcining it for 3-7 hours.
[0057] Generally speaking, as the temperature increases, the diffusion coefficient of the material increases, which promotes the diffusion of ions and vacancies, particle rearrangement and other material transfer processes, making the calcination speed faster. The temperature increase has little effect on the bulk density of the material, but has a greater effect on the tap density of the product. The increase in temperature, on the one hand, promotes the growth of primary particles in the product to be coarse and dense, and improves the tap density. In addition, many small agglomerated particles in the precursor that have not been spherical are also regrown into products with dense structures due to solid-phase reactions. Therefore, it is beneficial to the reaction to appropriately increase the calcination temperature. However, if the temperature is too high, it is easy to generate oxygen-deficient compounds and promote secondary recrystallization. At the same time, the grain size of the material becomes larger and the specific surface area becomes smaller, which is not conducive to the removal and embedding of metal ions in the material; if the temperature is too low, the reaction is incomplete, and it is easy to generate amorphous materials. The crystallization performance of the material is not good, and it is easy to contain impurities, which has a greater impact on the electrochemical properties of the material. Therefore, only when the calcination temperature is moderate can the processability and electrochemical properties of the material reach the best state. Through experimental determination, the calcination temperature is between 750 and 850 ° C, and the various properties are the best.
[0058] In some embodiments, the ZnMnO3 and MXene material are ball-milled with anhydrous ethanol at a mass ratio of 1:1, the ball-milling time is 14 to 26 hours, and the ball-milling speed is 280 to 320 rpm.
[0059] Specifically, 0.5-5 g of the ZnMnO3 and MXene materials are weighed in a stainless steel ball mill, and then 2.5-25 mL of anhydrous ethanol is added, and the mixture is ball milled at a speed of 300 rpm for 14-26 hours, and then the precipitate is collected, washed, and dried to obtain MXene / ZnMnO3. The ball milling method for preparing MXene / ZnMnO3 has the advantage of simple process, and the ZnMnO3 embedded in the MXene interlayer has an irregular particle structure, which significantly improves the specific surface area, pore volume, and average pore size of ZnMnO3, thereby improving the ORR performance.
[0060] In a preferred embodiment, 1 to 3 g of each of the ZnMnO3 and MXene materials are weighed into a stainless steel ball mill, and 5 to 15 mL of anhydrous ethanol are added, and ball milling is performed at a rotation speed of 300 rpm for 16 to 24 hours; wherein the ZnMnO3 and MXene materials have the same mass.
[0061] In addition, the present invention also provides a new catalytic material MXene / ZnMnO3, which is prepared by the preparation method of the new catalytic material MXene / ZnMnO3.
[0062] In this embodiment, the new catalytic material MXene / ZnMnO3 has a complete layered structure and a large interlayer spacing, which increases the specific surface area, pore volume and average pore size of ZnMnO3. By comparing the polarization curves, it can be seen that after adding MXene, the limiting current density increases significantly, and its ORR performance is significantly improved compared to pure zinc manganate.
[0063] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.
[0064] Example 1
[0065] Preparation of ZnMnO3:
[0066] Weigh Zn(NO3)2·6H2O and MnSO4·H2O, where [Zn 2+ ] and [Mn 2+ ] is 1:1, and the metal ion [Zn 2+ ] and [Mn 2+ ] is a mixed solution with a total concentration of 0.1mol / L. Na2CO3 is prepared into a Na2CO3 solution with a concentration of 0.2mol / L. First add an appropriate amount of deionized water to a beaker and start stirring (marked as base liquid), and drop the mixed solution and Na2CO3 solution into the base liquid at a rate of 3.2mL / min and 4.8mL / min respectively and continue stirring for 3h. During this period, a white precipitate is gradually formed. After another 4h of aging reaction, wash with anhydrous ethanol and deionized water, collect the precipitate after centrifugation, and place it in an oven until it is completely dry to obtain a white powder precursor. After grinding the precursor powder, heat it to 800℃ in a muffle furnace and calcine it for 4h, then grind it to obtain a black powder ZnMnO3.
[0067] Preparation of MXene / ZnMnO3:
[0068] Weigh 1 g of ZnMnO3 and MXene material respectively into a stainless steel ball mill, add 5 mL of anhydrous ethanol, and ball mill at 300 rpm for 20 hours. Collect the precipitate, wash and dry to obtain MXene / ZnMnO3.
[0069] Example 2
[0070] Preparation of ZnMnO3:
[0071] Weigh Zn(NO3)2·6H2O and MnSO4·H2O, where [Zn2+ ] and [Mn 2+ ] is 1:1, and the metal ion [Zn 2+ ] and [Mn 2+ ] is a mixed solution with a total concentration of 0.15mol / L. Na2CO3 is prepared into a Na2CO3 solution with a concentration of 0.3mol / L. First add an appropriate amount of deionized water to a beaker and start stirring (marked as base liquid), drop the mixed solution and the Na2CO3 solution into the base liquid at a rate of 3.5mL / min and 5.25mL / min respectively and continue stirring for 3.5h, during which a white precipitate is gradually formed. After 5h of aging reaction, wash with anhydrous ethanol and deionized water, collect the precipitate after centrifugation, place it in an oven until completely dry, and a white powder precursor can be obtained. After grinding, heat it to 820℃ in a muffle furnace and calcine it for 5h, then grind it to obtain a black powder ZnMnO3.
[0072] Preparation of MXene / ZnMnO3:
[0073] Weigh 2 g of ZnMnO3 and MXene materials respectively into a stainless steel ball mill, add 10 mL of anhydrous ethanol, and mill at 300 rpm for 22 hours. Collect the precipitate, wash and dry to obtain MXene / ZnMnO3.
[0074] Example 3
[0075] Preparation of ZnMnO3:
[0076] Weigh Zn(NO3)2·6H2O and MnSO4·H2O, where [Zn 2+ ] and [Mn 2+ ] is 1:1, and the metal ion [Zn 2+ ] and [Mn 2+ ] is a mixed solution with a total concentration of 0.2mol / L. Na2CO3 is prepared into a Na2CO3 solution with a concentration of 0.4mol / L. First add an appropriate amount of deionized water to a beaker and start stirring (marked as base liquid), and drop the mixed solution and the Na2CO3 solution into the base liquid at a rate of 4mL / min and 6mL / min respectively and continue stirring for 4h. During this period, a white precipitate can be seen gradually forming. After 5h of aging reaction, wash with anhydrous ethanol and deionized water, collect the precipitate after centrifugation, and place it in an oven until it is completely dry to obtain a white powder precursor. After grinding, heat it to 840℃ in a muffle furnace and calcine it for 6h, then grind it to obtain a black powder ZnMnO3.
[0077] Preparation of MXene / ZnMnO3:
[0078] Weigh 3 g of ZnMnO3 and MXene materials respectively into a stainless steel ball mill, add 15 mL of anhydrous ethanol, and mill at 300 rpm for 24 hours. Collect the precipitate, wash and dry to obtain MXene / ZnMnO3.
[0079] Comparative Example 1
[0080] Preparation of ZnMnO3:
[0081] Weigh Zn(NO3)2·6H2O and MnSO4·H2O, where [Zn 2+ ] and [Mn 2+ ] is 1:1, and the metal ion [Zn 2+ ] and [Mn 2+ ] is a mixed solution with a total concentration of 0.1mol / L. Na2CO3 is prepared into a Na2CO3 solution with a concentration of 0.2mol / L. First add an appropriate amount of deionized water to a beaker and start stirring (marked as base liquid), and drip the mixed solution and the Na2CO3 solution into the base liquid at a rate of 3.2mL / min and 4.8mL / min respectively and continue stirring for 3h. During this period, a white precipitate can be seen gradually forming. After another 4h of aging reaction, wash with anhydrous ethanol and deionized water, collect the precipitate after centrifugation, and place it in an oven until it is completely dry to obtain a white powder precursor. After grinding, heat it to 800℃ in a muffle furnace and calcine it for 4h, then grind it to obtain a black powder ZnMnO3.
[0082] The performance of MXene / ZnMnO3 prepared in Example 1 and ZnMnO3 prepared in Comparative Document 1 were characterized as follows:
[0083] like Figure 2 As shown, Figure 2 Scanning electron micrographs of MXene / ZnMnO3 prepared in Example 1 at different magnifications ((a) 50,000 times, (b) 100,000 times, (c) 300,000 times, (d) 400,000 times). Obviously, after ball milling, the spherical structure of zinc manganese oxide has been destroyed into irregular particles, while the accordion-like structure of MXene material has been ball milled into fragments. Figure 2 (c) and Figure 2 (d) It can be seen that zinc manganate particles are distributed between large pieces of MXene materials, and the particle size ranges from about 20 to 40 nm.
[0084] Figure 3 The X-ray powder diffraction patterns of ZnMnO3 and MXene / ZnMnO3 in Comparative Example 1 and Example 1 are shown. As can be seen from the figure, the main peak of MXene / ZnMnO3 prepared by ball milling is clearly visible, and the perovskite structure of ZnMnO3 is well maintained.
[0085] Figure 4 N2 adsorption-desorption curves of ZnMnO3 in Comparative Example 1 and Example 1 ( Figure 4 a) and N2 adsorption-desorption curves of MXene / ZnMnO3 ( Figure 4 b). As can be seen from the figure, the N2 adsorption and desorption curves of ZnMnO3 and MXene / ZnMnO3 do not overlap, and both have hysteresis loops at relatively high pressures, which are type IV adsorption and desorption isotherms. Both are mesoporous materials.
[0086] Figure 5 The pore size distribution curves of Comparative Example 1 and Example 1 show that the pore size of ZnMnO3 is mainly distributed around 1.80 nm, and the main range of the pore size distribution of MXene / ZnMnO3 is 1.71-8.78 nm. The addition of MXene material by ball milling significantly improves the specific surface area, pore volume and average pore size of ZnMnO3.
[0087] Figure 6 CV curves of ZnMnO3 and MXene / ZnMnO3 in Comparative Example 1 and Example 1 ( Figure 6 a) and ORR polarization curves ( Figure 6 b). Oxygen reduction peaks appear in the CV curves of ZnMnO3 and MXene / ZnMnO3 materials, indicating that both have ORR performance. However, the Tafel slope of MXene / ZnMnO3 is smaller, so its ORR performance is better. By comparing the polarization curves, it can be seen that after adding MXene, although the half-wave potential and the starting potential of the material have a slight negative shift, the limiting current density increases significantly, from -2.49 mA cm -2 Increased to -3.36 mA cm -2 It can be seen that its ORR performance is significantly improved compared with pure zinc manganese oxide.
[0088] In summary, the present invention provides a new catalytic material MXene / ZnMnO3 and a preparation method thereof, wherein the new catalytic material MXene / ZnMnO3 is prepared by ball milling, and the zinc manganate in MXene / ZnMnO3 has an irregular particle structure; the ball milling method is used to prepare the MXene material as a carrier, and the perovskite-type oxide ZnMnO3 is embedded in the interlayer, so that the specific surface area, pore volume and average pore size of ZnMnO3 are significantly improved, and the interlayer spacing can be increased while maintaining the layered structure of the MXene material, the path of ion diffusion and charge transfer is widened, and the electrochemical performance of the MXene material is improved, thereby improving the overall catalytic performance of the catalyst. By comparing the polarization curves, it can be seen that after adding the MXene material, its limiting current density increases significantly, and the ORR performance is greatly improved compared to pure zinc manganate.
[0089] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a new catalytic material MXene / ZnMnO3, characterized in that: Includes steps: Prepare a mixed solution of Zn(NO3)2·6H2O and MnSO4·H2O; prepare a Na2CO3 solution; Using deionized water as the base liquid, dripping the mixed solution and the Na2CO3 solution into the base liquid and stirring, and generating a precipitate through an aging reaction; The precipitate is washed and centrifuged, and then dried to obtain a precursor powder; The precursor powder is ground, calcined, and then ground to obtain ZnMnO3; The ZnMnO3 and MXene materials are ball-milled with anhydrous ethanol at a mass ratio of 1:1, the ball-milling time is 14 to 26 hours, and the ball-milling speed is 280 to 320 rpm; The ball-milled material is collected, washed and dried to obtain the MXene / ZnMnO3; The mixed solution contains [Zn 2+ ] and [Mn 2+ ] is 1:1; the metal ions [Zn 2+ ] and [Mn 2 + ] has a total concentration of 0.1 to 0.3 mol / L; the concentration of the Na2CO3 solution is 0.2 to 0.6 mol / L; The concentration of the Na2CO3 solution is greater than that of the mixed solution, and the concentration ratio of the mixed solution to the Na2CO3 solution is 1:(2-3); the speed ratio of the mixed solution to the Na2CO3 solution dripping into the base solution is 2:(3-4).
2. The method for preparing the novel catalytic material MXene / ZnMnO3 according to claim 1, characterized in that: The mixed solution and the Na2CO3 solution are dropped into the base solution at a rate of 2-6 mL / min and 3-9 mL / min, respectively, and stirred for 2-4 hours.
3. The method for preparing the novel catalytic material MXene / ZnMnO3 according to claim 1, characterized in that: The aging reaction time is 2 to 6 hours.
4. The method for preparing the novel catalytic material MXene / ZnMnO3 according to claim 1, characterized in that: The calcination process comprises the steps of: The precursor powder is ground, placed in a muffle furnace and heated to 700-900° C., and the calcination time is 2-8 hours.
5. A new catalytic material MXene / ZnMnO3, characterized in that: The MXene / ZnMnO3 catalyst is prepared by the method for preparing the new catalytic material as described in any one of claims 1 to 4.
Citation Information
Patent Citations
Method for preparing spinel lithium manganate through ball milling
CN105152220A
Preparation method for anode material ZnMnO3 of lithium ion battery
CN104934592A
Air electrode catalyst nano hexagonal ZnMnO3 preparation method and application
CN107792884A
Preparation and application of self-supporting two-dimensional MXene@ZnMn2O4 composite electrode material
CN110299523A